A new species of Hemiphyllodactylus (Squamata: Gekkonidae) from Hong Kong - Sung, Yik-Hei; Lee, Wing-Ho; Ng, Ho-Nam; Zhang, Yanjie; Yang, Jian-Huan (Zootaxa, 2018)
A new species of gekkonid, Hemiphyllodactylus hongkongensis sp. nov., is described based on a series of specimens collected from Hong Kong SAR, China. The new species can be distinguished from other known congeners by molecular divergence in the mitochondrial ND2 gene and morphological characters including 5–6 chin scales; a manual lamellar formula of 3–3(4)–4–4; a pedal lamellar formula of 3(4)–4(5)–4(5)–4; 24–25 continuous femoral and precloacal pores; 12–15 dorsal scales and 9–10 ventral scales contained in diameter of eye. At present, the genus Hemiphyllodactylus comprises 22 described species.